Use of Lacrimal Symptoms Questionnaire After Punctoplasty Surgery: Retrospective Data of Technical Strategy. Issue 8 (7th November 2021) - Meduri, Alessandro; Tumminello, Giuseppe; Oliverio, Giovanni William; Inferrera, Leandro; Delia, Gabriele; Aragona, Pasquale; Cicciù, Marco
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The goal of this study is to evaluate postpunctoplasty symptoms with lacrimal symptoms questionnaire (Lac-Q). A retrospective study was conducted on 31 patients (14 men and 17 woman) with a diagnosis of canalicular stenosis: 26 patients with unilateral occlusion and 5 patients with bilateral occlusion. The Lac-Q was administered preoperative and at 1, at 3, and at 6 months following the surgery. Moreover, the Lac-Q questionnaire was administered by an independent observer (SI). The mono-lateral and bilateral postoperative Lac-Q score showed a significant improvement of symptoms at 1, 3, and 6 months than the preoperative results. The Lac-Q questionnaire is a way to evaluate the quality of outcomes after punctoplasty surgery. In this study, all patients showed a significant improvement of symptoms after surgery.